The Impact of Human Activities on the Ndivana Forest Reserves, Kwaya Kusar Local Government Area, Borno State, Nigeria - Dami, Anthony; Daniel, Balami Huali; S.S, Garba (International Journal of Geography and Geology, 2017)
The focus of this study is to assess the effects of human activities on the Ndivana forest Reserves in Borno State. The types of data collected for the study involves the satellite imageries of Landsat (MSS) 1976, 1986 (TM) and Enhanced Thematic Mapper plus (ETM+) 1999, 2005, 2009 and 2013 respectively, from Global Lat-sat Cover Facility (GLCF) on Earth Science data interface. The GIS software used for the analysis of the datasets include: ILWIS 3.3a to geo-reference and image classification while, ArcGIS 10.1 was used for area calculation and over lay operations. The study adopted six land use and land cover classification scheme (namely, agriculture, bare surface, shrub/grassland, swamp, settlement and wood land). The major findings reported that the land use and land cove change for the period of 37years showed an increase and declining trends. For example, it was observed that agriculture increases in 1986 and 2009 with 3.84km2(7.21%) and 3.86km2(7.23%) because of the increase in human population that engaged in farming activities in the area and decreases in 2013 with 1.40km2(2.61%) due to increase in bare surface. Settlement also increases sharply in 1999 with 7.81km (14.75%) and decreases to 4.17km (7.79%) in 2013 due to the problems of insecurity in the region as many communities relocated to a safer environment. The implication of this change on the forest ecosystem therefore, could lead to further environmental degradation and biodiversity lost in the area.